Pengkajian Tingkat Kelelahan Petugas Air Traffic Controller (ATC) Dalam Meberikan Pelayanan Lalu Lintas PEnerbangan di Bandara Juanda Surabaya - Susanti Susanti (Research and Development Agency of The Ministry of Transportation, 2011)
Assessment of Air Traffic Controllers (ATC) Fatigue Level in Providing flight Traffic services at Juanda International Airport Surabaya is to know how the description of Air traffic controller fatigue level in guiding services air traffic that impact on aviation safety. Assessment method used descriptive quantitative method by using Paired Sample T-Tesf method analysis, comparing the condition of fatigue before and after the ATC on duty, as well as exposure and detailed explanation based on the primary and secondary data compilation and the data have been processed. The assessment result shows that there are level of fatigue of Air Traffic Controller that significant, both of physical and psychological factors.